Problematika Non-Linguistik Pembelajaran Bahasa Arab Kurikulum 2013 Pascapandemi Covid-19 di MI Darul Ulum Ngaliyan Semarang - Humaidah Humaidah; Luthfiyah Khoirun Nisa’ (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
This research aims to describe the non-linguistic problems of implementing the 2013 curriculum in Arabic learning at MI Darul Ulum Ngaliyan Semarang after the COVID-19 pandemic and efforts to overcome them. The method used in this research is descriptive qualitative. Data were collected by interview and documentation. Non-linguistic problems are found in the process of learning activities and human resources. The problems of learning activities include interaction patterns, learning models and techniques, learning media, assessments, teaching materials, and learning processes. The problems of human resources are in the teacher and heterogeneity of students, low interest in learning Arabic, and lack of understanding of students in Arabic. Therefore, teachers must prepare, develop, and make learning Arabic as good and interesting as possible so that students become excited to learn Arabic.